Rapid crosslinking type carbon fiber precursor oiling agent based on reversible ion hydrogen bonds and preparation method thereof
By using crosslinked silicone oil agent based on reversible ion hydrogen bonds in the carbon fiber manufacturing process, the flow problem of the oil film in the pre-oxidation process is solved, and the uniform distribution of the oil film and the improvement of the carbon fiber strength is achieved.
Patent Information
- Application Number
- CN202311305293.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-11
AI Technical Summary
During the existing carbon fiber manufacturing process, the oil film on the surface of the raw silk is prone to flow under high temperature conditions in the pre-oxidation process, resulting in uneven distribution of the oil film, increasing the surface defects of the carbon fiber and reducing the strength.
A crosslinked silicone oil agent based on reversible ion hydrogen bonds is used. The oil agent does not undergo crosslinking reactions during the spinning stage, which improves the passability of the spinning process; in the preoxidation stage, the carboxyl group and amino group undergo rapid dehydration and condensation reaction to form a crosslinked oil film, inhibiting the flow of the oil film and improving the distribution uniformity.
It effectively inhibits the flow of oil film during the pre-oxidation process, reduces the surface defects of carbon fibers, and improves the strength and quality of carbon fibers.
Smart Images

Figure CN119800720A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon fiber material preparation, and in particular relates to a fast cross-linking carbon fiber precursor oil agent based on reversible ionic hydrogen bonds and a preparation method thereof. Background Art
[0002] The carbon fiber manufacturing process usually requires the original silk bundle to be heated in an oxygen atmosphere below 200°C to 400°C to be converted into a pre-oxidized silk bundle (pre-oxidation process), and then carbonized in an inactive atmosphere above 1000°C (carbonization process). In the above-mentioned pre-oxidation process and initial carbonization process, single fibers are prone to welding, fuzzing and wire breakage. In order to prevent welding between single fibers, a known method is to coat the surface of the original silk bundle with a layer of heat-resistant oil film (oil treatment). The oil treatment mainly uses an aqueous silicone emulsion, and its main component is a functional polysiloxane with excellent high temperature resistance. The oil treatment can not only prevent the adhesion between polyacrylonitrile precursor, pre-oxidized silk and carbon filaments, but also reduce the friction between metal and fiber during the carbon fiber manufacturing process, help eliminate the static charge accumulated during the fiber processing process, increase the bonding between fibers, ensure the smooth progress of the carbon fiber manufacturing process, and reduce the surface defects of carbon fiber. However, the oil film attached to the surface of the raw fiber is prone to flow under the high temperature conditions of the pre-oxidation process, resulting in uneven distribution of the oil film on the surface of the pre-oxidized fiber, thereby increasing the surface defects of the pre-oxidized fiber and reducing the strength of the carbon fiber.
[0003] The known solution to prevent the oil film from flowing is to use a cross-linked silicone emulsion to inhibit the oil film from flowing during the pre-oxidation process, reduce the uneven distribution of the oil film on the surface of the pre-oxidation fiber and reduce the diffusion of the silicone emulsion into the original fiber, which is beneficial to reduce the defects of the carbon fiber and improve the strength of the carbon fiber. Chinese patent CN 107829306 BA discloses a coated carbon fiber original fiber oil agent, in which the amino polydimethylsiloxane and epoxy-modified polydimethylsiloxane in the main component undergo a ring-opening cross-linking reaction at high temperature to achieve oil film cross-linking. However, its reaction rate is too slow, resulting in a sticking phenomenon in the spinning stage, causing damage to the fiber surface. In order to increase the cross-linking rate of the oil agent, Chinese patent CN 114622417A discloses a fast cross-linking film-forming carbon fiber spinning oil agent, in addition to amino polydimethylsiloxane and epoxy-modified polydimethylsiloxane, the oil agent component also includes an aminosilane coupling agent and a catalyst to increase the cross-linking rate of the oil film, effectively reducing the sticking phenomenon of the oil agent in the spinning stage. However, the introduction of aminosilane coupling agent can easily cause adhesion between the filaments in the precursor tow, which not only damages the fiber surface and causes surface defects, but also hinders the release of reaction heat during the pre-oxidation process, causing heat storage, overheating and fiber melting. Therefore, it is urgent to develop new strategies to inhibit the flow of the oil film attached to the surface of the precursor during the pre-oxidation process, while ensuring the smooth progress of the spinning process. Summary of the invention
[0004] The present invention aims to provide a cross-linked silicone oil agent based on reversible ionic hydrogen bonds. The cross-linked silicone oil agent is used for carbon fiber spinning. No cross-linking reaction occurs in the spinning stage, so the passability of the spinning process can be improved and the sticking to the roller phenomenon in the spinning stage can be suppressed. In the pre-oxidation stage, the oil film formed on the surface of the raw silk using the oil agent can quickly undergo a cross-linking reaction to form a cross-linked oil film, which inhibits the flow of the oil film during the pre-oxidation process and reduces the uneven distribution of the oil film on the surface of the pre-oxidation silk fiber, which is beneficial to reducing the defects of the carbon fiber and improving the strength of the carbon fiber.
[0005] The cross-linked organic silicone oil agent based on reversible ionic hydrogen bonds provided by the present invention comprises a basic component, a nonionic emulsifier and an auxiliary agent.
[0006] The base component comprises: an amino-modified polydimethylsiloxane (A) represented by formula (1a) and a carboxyl-modified polydimethylsiloxane (B), wherein the carboxyl-modified polydimethylsiloxane (B) is at least one selected from the group consisting of a dicarboxyl-terminated polydimethylsiloxane (B1) represented by the following formula (2b) and a monocarboxyl-terminated polydimethylsiloxane (B2) represented by formula (3c);
[0007] The molar ratio of the carboxyl content in the carboxyl-modified polydimethylsiloxane (B) to the amino content in the amino-modified polydimethylsiloxane (A) is 0.2 or more and 1.0 or less;
[0008]
[0009] In formula (1a), ma is an arbitrary number greater than or equal to 1, more preferably an arbitrary number greater than or equal to 10 and less than or equal to 300, and further preferably an arbitrary number greater than or equal to 50 and less than or equal to 150;
[0010] In addition, na is an arbitrary number greater than or equal to 1, more preferably an arbitrary number greater than or equal to 2 and less than or equal to 10, and further preferably an arbitrary number greater than or equal to 2 and less than or equal to 5;
[0011] ra is 0 or 1; when ra is 0, pa is 0; when ra is 1, pa is any number greater than 1 and less than 5;
[0012] sa is any number greater than 1 and less than 5;
[0013] Further, the dimethylsiloxane units and the methylaminoalkylsiloxane units are randomly arranged;
[0014] When na and ma in the formula (1a) are within the above ranges, the oil can obtain sufficient heat resistance, bundling properties, and fiber splitting properties.
[0015] Furthermore, when ma is 10 or more, sufficient heat resistance can be obtained and fusion between single fibers can be effectively prevented.
[0016] When ma is at most 300, it is easy to emulsify the polyol into a stable aqueous emulsion using a nonionic emulsifier.
[0017] Furthermore, when na is 2 or more, sufficient affinity with the original yarn can be ensured, and fusion between single fibers can be effectively prevented.
[0018] Furthermore, when na is 10 or less, the base component itself has sufficient heat resistance and can prevent fusion between single fibers.
[0019] In formula (1a), ra is 0 or 1. When ra is 0, pa is 0, and sa is preferably greater than 1 and less than 5, and more preferably the amino group is modified into an aminopropyl group, that is, sa is 3; when ra is 1, pa is greater than 1 and less than 5, and more preferably β-(aminoethyl)-γ-aminopropyl.
[0020] In addition, the amino-modified silicone represented by formula (1a) may be a mixture of a plurality of compounds. Therefore, each of na, ma, pa, ra and sa may not be an integer.
[0021] The kinetic viscosity of the amino-modified polydimethylsiloxane (A) at 25° C. is preferably 50 mPa·s or more and 3500 mPa·s or less, and more preferably 80 mPa·s or more and 3000 mPa·s or less.
[0022] When the dynamic viscosity is 50 mPa·s or more, sufficient bundling properties can be imparted to the original yarn.
[0023] On the other hand, when the dynamic viscosity is 3500 mPa·s or less, it is easy to emulsify the liquid into a stable aqueous emulsion using a nonionic emulsifier.
[0024] The amino group content of the amino-modified polydimethylsiloxane (A) is preferably 0.05 mmol / g or more and 1.0 mmol / g or less, and more preferably 0.1 mmol / g or more and 0.8 mmol / g or less.
[0025] If the amino content is 0.05 mmol / g or more, the amino-modified polydimethylsiloxane (A) has good affinity with the precursor and can be uniformly attached to the surface of the precursor. On the other hand, if the amino content is 1.0 mmol / g or less, the amino-modified polydimethylsiloxane has sufficient thermal stability. If the amino equivalent is within the above range, both the affinity with the precursor and the thermal stability of the basic component can be taken into account.
[0026]
[0027] In formula (2b), nb is an arbitrary number of 1 or more, more preferably 10 or more and 300 or less, and further preferably 50 or more and 150 or less.
[0028] If nb is greater than 10, the dicarboxyl-terminated polydimethylsiloxane (B1) and the amino-modified polydimethylsiloxane (A) undergo a cross-linking reaction to form an elastic oil film; if nb is less than 300, after the carboxyl group of the dicarboxyl-terminated polydimethylsiloxane (B1) and the amino group of the amino-modified polydimethylsiloxane (A) form a reversible ionic hydrogen bond, the viscosity of the mixture is low and it is easy to emulsify it into a stable aqueous emulsion by a non-ionic emulsifier.
[0029] The dynamic viscosity of the dicarboxyl-terminated polydimethylsiloxane (B1) at 25° C. is preferably 100 mPa·s or more and 3000 mPa·s or less, and more preferably 200 mPa·s or more and 2000 mPa·s or less.
[0030] The carboxyl group content of the dicarboxyl-terminated polydimethylsiloxane (B1) is preferably 0.1 mmol / g or more and 2.0 mmol / g or less, and more preferably 0.2 mmol / g or more and 1.5 mmol / g or less.
[0031] If the carboxyl content is 0.1 mmol / g or more, the dicarboxyl-terminated polydimethylsiloxane (B1) and the amino-modified polydimethylsiloxane (A) can undergo a crosslinking reaction to form an elastic oil film. On the other hand, if the carboxyl content is 2.0 mmol / g or less, the carboxyl groups of the dicarboxyl-terminated polydimethylsiloxane (B1) and the amino groups of the amino-modified polydimethylsiloxane (A) form reversible ionic hydrogen bonds, and the viscosity of the mixture is low, and it is easy to emulsify it into a stable aqueous emulsion by a nonionic emulsifier.
[0032]
[0033] In formula (3c), nc is an arbitrary number of 1 or more, more preferably 5 or more and 200 or less, and further preferably 10 or more and 100 or less. m is an arbitrary number of 1 or more and 10 or less (including 10).
[0034] If nc is greater than 5, the monocarboxyl-terminated polydimethylsiloxane (B2) and the amino-modified polydimethylsiloxane (A) undergo a cross-linking reaction to form an elastic oil film; if nc is less than 200, after the carboxyl group of the monocarboxyl-terminated polydimethylsiloxane (B2) and the amino group of the amino-modified polydimethylsiloxane (A) form a reversible ionic hydrogen bond, the viscosity of the mixture is low and it is easy to emulsify it into a stable aqueous emulsion through a non-ionic emulsifier.
[0035] The kinetic viscosity of the monocarboxyl-terminated polydimethylsiloxane (B2) at 25°C is preferably 50 mPa·s or more and 2000 mPa·s or less, and more preferably 100 mPa·s or more and 1500 mPa·s or less.
[0036] The carboxyl group content of the monocarboxyl-terminated polydimethylsiloxane (B2) is preferably 0.05 mmol / g or more and 1.5 mmol / g or less, and more preferably 0.07 mmol / g or more and 1.2 mmol / g or less.
[0037] If the carboxyl content is 0.05 mmol / g or more, the dicarboxyl-terminated polydimethylsiloxane (B1) and the amino-modified polydimethylsiloxane (A) can rapidly undergo a crosslinking reaction to form an elastic oil film. On the other hand, if the carboxyl content is 1.5 mmol / g or less, the carboxyl groups of the dicarboxyl-terminated polydimethylsiloxane (B1) and the amino groups of the amino-modified polydimethylsiloxane (A) form reversible ionic hydrogen bonds, and the viscosity of the mixture is low, and it is easy to emulsify it into a stable aqueous emulsion by a nonionic emulsifier.
[0038] The carboxyl-modified polydimethylsiloxane (B) is one or more selected from the group consisting of a dicarboxyl-terminated polydimethylsiloxane (B1) represented by formula (2b) and a monocarboxyl-terminated polydimethylsiloxane (B2) represented by formula (3c), and the mass ratio of the dicarboxyl-terminated polydimethylsiloxane (B1) to the monocarboxyl-terminated polydimethylsiloxane (B2) is arbitrary.
[0039] In the cross-linked silicone oil based on reversible ionic hydrogen bonds, the nonionic emulsifier is selected from one or more of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, oil polyoxyethylene ether, polyoxyethylene sorbitan ester, and alkyl alcohol amide polyoxyethylene ether.
[0040] The content of the nonionic emulsifier is preferably 10 parts by mass or more and 100 parts by mass or less, and more preferably 20 parts by mass or more and 65 parts by mass or less, relative to 100 parts by mass of the essential component.
[0041] If the content of the nonionic emulsifier is 10 parts by mass or more, the basic component can be easily emulsified into a stable aqueous emulsion; on the other hand, if the content of the nonionic emulsifier is 100 parts by mass or less, the reduction in the bundling of the precursor to which the oil composition is attached can be suppressed. In addition, the mechanical properties of the carbon fiber tow prepared from the precursor tow are not easily reduced.
[0042] In the cross-linked organic silicone oil based on reversible ionic hydrogen bonds, the auxiliary agents include antistatic agents and antioxidants, which are any auxiliary agents disclosed in the prior art that are applicable to carbon fiber precursors.
[0043] The content of the antioxidant is preferably 0.5 parts by mass or more and 5 parts by mass or less, and more preferably 1 part by mass or more and 3 parts by mass or less, relative to the total mass of the base component and the nonionic emulsifier.
[0044] When the content of the antioxidant is 0.5 parts by mass or more, a sufficient antioxidant effect can be obtained. On the other hand, when the content of the antioxidant is 5 parts by mass or less, the antioxidant can be easily uniformly dispersed in the oil composition.
[0045] Various known antioxidants can be used, but phenol-based antioxidants are preferred.
[0046] Specific examples of the phenolic antioxidant include triethylene glycol bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate], pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanurate, 4,4'-butylenebis(6-tert-butyl-3-methylphenol), 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 2,6-di-tert-butyl-4-ethylphenol, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 2,6-di-tert-butyl-p-cresol, and tetrakis[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate]methane. These antioxidants may be used alone or in combination of two or more.
[0047] The content of the antistatic agent is preferably 0.5 parts by mass or more and 5 parts by mass or less relative to the total mass of the base component and the nonionic emulsifier.
[0048] As the antistatic agent, known antistatic agents can be used.
[0049] Ionic antistatic agents are preferred, among which alkyl quaternary ammonium salts, aliphatic sulfonates, higher alcohol sulfuric acid ester salts, higher alcohol ethylene oxide adduct sulfuric acid ester salts, higher alcohol phosphate ester salts, higher alcohol ethylene oxide adduct sulfuric acid phosphate ester salts, higher alcohol ethylene oxide adduct polyethylene glycol fatty acid esters, polyol fatty acid esters, etc. are preferably used. These antistatic agents can be used alone or in combination of two or more.
[0050] The application of the above cross-linked silicone oil based on reversible ionic hydrogen bonds in the manufacture of carbon fibers also falls within the protection scope of the present invention.
[0051] The invention also provides an oil treatment liquid suitable for carbon fiber manufacturing.
[0052] The oil treatment liquid suitable for carbon fiber manufacturing is prepared by dispersing (emulsifying) the above-mentioned cross-linked silicone oil agent based on reversible ionic hydrogen bonds (including a base component, a nonionic emulsifier and an auxiliary agent) in water.
[0053] The average particle size of the emulsified particles of the oil treatment liquid is preferably 0.01 μm or more and 0.3 μm or less.
[0054] When the average particle size of the emulsified particles is within the above range, the oil solution can be more uniformly attached to the surface of the raw yarn.
[0055] The oil treatment liquid is prepared by a method comprising the following steps:
[0056] The base component, nonionic emulsifier and auxiliary agent are stirred evenly, and then water is added dropwise to the mixture at a certain dropping speed while stirring to obtain an emulsion (water emulsion) in which the oil agent is dispersed in water.
[0057] The components can be mixed or dispersed in water using a mechanical stirrer, homomixer, homogenizer, etc. When a high-viscosity oil is used to prepare an aqueous emulsion, it is preferred to use an ultrahigh-pressure homogenizer capable of applying pressure to 150 MPa or more.
[0058] The concentration of the oil agent in the aqueous emulsion is preferably 10% by mass or more and 40% by mass or less, and more preferably 20% by mass or more and 40% by mass or less.
[0059] The obtained aqueous emulsion can be used as an oil treatment liquid as it is, but it is preferred to further dilute the aqueous emulsion to a predetermined concentration before using it as an oil treatment liquid.
[0060] The present invention has the following effects:
[0061] According to the present invention, reversible ionic hydrogen bonds are formed between the carboxyl groups and the amino groups in the basic components of the oil agent, and the basic components do not undergo a cross-linking reaction in the spinning stage. As a result, the passability of the spinning process can be improved and the sticking to the roller phenomenon in the spinning stage can be suppressed. In the pre-oxidation stage, the carboxyl groups and the amino groups rapidly undergo a dehydration condensation reaction to form an amide bond. Therefore, the oil film formed on the surface of the raw silk using the oil agent can rapidly undergo a cross-linking reaction to form a cross-linked oil film. The rapid cross-linking of the oil film can suppress the flow of the oil film during the pre-oxidation process and reduce the uneven distribution of the oil film on the surface of the pre-oxidation silk fiber, which is beneficial to reducing the defects of the carbon fiber and improving the strength of the carbon fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 It is the chemical structural formula of epoxy-modified polysiloxane X-22-163C. DETAILED DESCRIPTION
[0063] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.
[0064] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.
[0065] The preparation method of the dicarboxyl-modified polysiloxane in the embodiment is as follows:
[0066] Into a 250ml three-necked flask, 36g (9mmol) of terminal hydrogenated polydimethylsiloxane (hydrogen content 0.05wt%), 36g of toluene, and 100ppm of platinum catalyst (relative to the mass of terminal hydrogenated polydimethylsiloxane) were added. After sufficient stirring, the temperature was raised to 85°C. Under nitrogen protection, 2.52g (18mmol) of allyl succinic anhydride was slowly dripped in. After complete dripping, the reaction was carried out at 85°C for 1 hour, and then the temperature was raised to 110°C and the reaction was continued for 6 hours. After the temperature dropped to room temperature, 0.648g (36mmol) of pure water was added. After sufficient stirring, the temperature was raised to 60°C, and stirred at this temperature for 2 hours. Water and toluene were removed under reduced pressure on a rotary evaporator to obtain a colorless and transparent product, i.e., dicarboxyl-terminated polydimethylsiloxane (nb≈54, carboxyl content of 0.9mmol / g, viscosity of 1600mPa·s).
[0067] The oil evaluation method in the following examples is:
[0068] <Measurement of oiling rate>
[0069] After the original silk was dried at 105°C for 1 hour, the mass fraction of the oil attached to the original silk was extracted by Soxhlet extraction. The specific method is: a certain mass (W 1 ) was added to a Soxhlet extractor, methyl ethyl ketone was added as a solvent, and the methyl ethyl ketone was heated to 90°C to reflux for 8 hours to extract the attached oil. After extraction, it was dried at 105°C for 2 hours. The mass of the raw silk was W 2 The oil pick-up rate was calculated by the following formula (i).
[0070] Oiling rate (mass %) = (W 1 -W 2 ) / W 1 ×100···(i)
[0071] <Evaluation of Drying Roll Sticking>
[0072] The sticking state of the drying roll during the production process of the raw yarn bundle was visually observed, and the bundling property was evaluated according to the following evaluation criteria.
[0073] A: Non-stick roller, that is, the spinning process runs continuously for one week, and no cross-linking oil agent is attached to the drying roller.
[0074] B: Slightly sticky to the roller, that is, the spinning process runs continuously for one week, and a small amount of cross-linked oil is attached to the drying roller.
[0075] C: Severe roller sticking, that is, the spinning process runs continuously for a week, and a large amount of cross-linked oil is attached to the drying roller, causing the yarn bundle to become fuzzy and broken.
[0076] <Determination of the degree of cross-linking of oil agents>
[0077] A certain mass (W 3 The oiled raw silk was kept at 240°C for 5 minutes, then cooled to room temperature, and Soxhlet extraction was performed according to the above oiling rate test method. After extraction, it was dried at 105°C for 2 hours. The mass of the raw silk was W 4 The degree of crosslinking was calculated by the following formula (ii).
[0078] Crosslinking degree (mass %) = [1-(W 3 -W 4 ) / W 3 ×100 / oiling rate]×100···(ii)
[0079] <Cluster Evaluation>
[0080] The state of the raw yarn bundle on the roller immediately before the bundle was wound onto the bobbin during the production process of the raw yarn bundle was visually observed, and the bundling property was evaluated according to the following evaluation criteria.
[0081] A: Excellent bundling properties, that is, the width of the tow is uniform and does not touch adjacent tows.
[0082] B: The bundle is average, the bundle width is inconsistent or the bundle width becomes wider.
[0083] C: Poor bundling, there is space in the tow, and the tow is not bundled.
[0084] Example 1
[0085] 75 parts by mass of amino-modified polydimethylsiloxane (A) (ma≈72, na≈3, pa=3, ra=1, sa=2, DY-N322 from Shandong Dayi Chemical Co., Ltd.) (180 mPa·s, amino content 0.5 mmol / g), 25 parts by mass of monocarboxyl-modified polydimethylsiloxane (B2) (m=10, nc≈14, Dow Corning DOWSIL TMBY 16-750Fluid) (140mPa·s, carboxyl content 1.2mmol / g) was mixed evenly, and then 50 parts by mass of isotridecanol polyoxyethylene ether (polyoxyethylene ether chain number 7) and 1 part by mass of antistatic agent (methyl trihydroxyethyl methylammonium sulfate) and 1 part by mass of antioxidant (tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester) were added, and 355 parts by mass of water were added dropwise while mechanically stirring to obtain an emulsion of a cross-linked silicone oil agent based on reversible ionic hydrogen bonds (the concentration of the oil agent in the emulsion was 30wt%).
[0086] Example 2
[0087] 85 parts by weight of amino-modified polydimethylsiloxane (A) (ma≈72, na≈3, pa=3, ra=1, sa=2, DY-N322 from Shandong Dayi Chemical Co., Ltd.) (180 mPa·s, amino content 0.5 mmol / g), 15 parts by weight of monocarboxyl-modified polydimethylsiloxane (B2) (same as above) (m=10, nc≈14, Dow Corning DOWSIL TM BY 16-750Fluid) (140mPa·s, carboxyl content 1.2mmol / g) was mixed evenly, and then 45 parts by mass of nonylphenol polyoxyethylene ether (polyoxyethylene ether chain number is 9) and 1 part by mass of antistatic agent (methyl trihydroxyethyl methylammonium sulfate) and 1 part by mass of antioxidant tetrakis [β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester) were added, and water (343 parts by mass) was added dropwise while mechanically stirring to obtain an emulsion of a cross-linked silicone oil agent based on reversible ionic hydrogen bonds (the concentration of the oil agent in the emulsion is 30wt%).
[0088] Example 3
[0089] 80 parts by weight of amino-modified polydimethylsiloxane (A) (ma≈140, na≈3, pa=3, ra=1, sa=2, DY-N322D2 from Shandong Dayi Chemical Co., Ltd.) (680 mPa·s, amino content 0.28 mmol / g) and 20 parts by weight of dicarboxyl-modified polydimethylsiloxane (B1) (self-made, nb≈54, carboxyl content 0.9 mmol / g, viscosity 1600 mPa·s) were mixed evenly, and then 50 parts by weight of C 12 ~C 18 Alcohol polyoxyethylene ether (polyoxyethylene ether chain number is 9, AEO-9), 1 part by mass of antistatic agent (methyl trihydroxyethyl methylammonium sulfate) and 1 part by mass of antioxidant (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), 343 parts by mass of water are added dropwise while mechanically stirring to obtain an emulsion of a cross-linked silicone oil agent based on reversible ionic hydrogen bonds.
[0090] Example 4
[0091] 88 parts by weight of amino-modified polydimethylsiloxane (A) (ma≈65, na≈1, pa=0, ra=0, sa=3, Shin-Etsu Silicone International Trading (Shanghai) Co., Ltd. KF-865) (110 mPa·s, amino content 0.20 mmol / g), 12 parts by weight of monocarboxyl-modified polydimethylsiloxane (B2) (m=10, nc≈14, Dow Corning DOWSIL TM BY 16-750 Fluid) (140 mPa·s, carboxyl content 1.2 mmol / g) was mixed evenly, and then 60 parts by mass of C 12 ~C 18 Alcohol polyoxyethylene ether (polyoxyethylene ether chain number is 9, AEO-9), 1 part by mass of antistatic agent (methyl trihydroxyethyl methyl ammonium sulfate) and 1 part by mass of antioxidant (2,2'-methylene bis (4-methyl-6-tert-butylphenol)), water (378 parts by mass) is added dropwise while mechanically stirring to obtain an emulsion of a cross-linked silicone oil agent based on reversible ionic hydrogen bonds (the concentration of the oil agent in the emulsion is 30wt%).
[0092] Example 5
[0093] 85 parts by mass of amino-modified polydimethylsiloxane (A)) (ma≈140, na≈3, pa=3, ra=1, sa=2, DY-N322D2 from Shandong Dayi Chemical Co., Ltd.) (680 mPa·s, amino content 0.28 mmol / g), 15 parts by mass of monocarboxyl-modified polydimethylsiloxane (B2) (m=10, nc≈14, Dow Corning DOWSIL TM BY 16-750 Fluid) (140 mPa·s, carboxyl content 1.2 mmol / g) was mixed evenly, and then 60 parts by mass of C 12 ~C 18 Alcohol polyoxyethylene ether (polyoxyethylene ether chain number is 9, AEO-9), 1 part by mass of antistatic agent (methyl trihydroxyethyl methyl ammonium sulfate) and 1 part by mass of antioxidant (2,2'-methylene bis (4-methyl-6-tert-butylphenol)), water (378 parts by mass) is added dropwise while mechanically stirring to obtain an emulsion of a cross-linked silicone oil agent based on reversible ionic hydrogen bonds (the concentration of the oil agent in the emulsion is 30wt%).
[0094] Example 6
[0095] 85 parts by mass of amino-modified polydimethylsiloxane (A)) (ma≈65, na≈1, pa=0, ra=0, sa=3, Shin-Etsu Silicone International Trading (Shanghai) Co., Ltd. KF-865) (110 mPa·s, amino content 0.20 mmol / g) and 15 parts by mass of dicarboxyl-modified polydimethylsiloxane (B1) (self-made, nb≈54, carboxyl content 0.9 mmol / g, viscosity 1600 mPa·s) were mixed uniformly, and then 55 parts by mass of isotridecyl alcohol polyoxyethylene ether (polyoxyethylene ether chain number 7) and 1 part by mass of antistatic agent (methyl trihydroxyethyl methylammonium sulfate) and 1 part by mass of antioxidant (2,2'-methylenebis(4-methyl-6-tert-butylphenol)) were added, and water (366 parts by mass) was added dropwise while mechanically stirring to obtain an emulsion of a cross-linked silicone oil agent based on reversible ionic hydrogen bonds (the concentration of the oil agent in the emulsion was 30 wt%).
[0096] Example 7
[0097] 70 parts by mass of amino-modified polydimethylsiloxane (A) (ma≈72, na≈3, pa=3, ra=1, sa=2, DY-N322 of Shandong Dayi Chemical Co., Ltd.) (180 mPa·s, amino content 0.5 mmol / g) and 30 parts by mass of dicarboxyl-modified polydimethylsiloxane (B1) (self-made, nb≈54, carboxyl content 0.9 mmol / g, viscosity 1600 mPa·s) were mixed uniformly, and then 60 parts by mass of isotridecyl alcohol polyoxyethylene ether (polyoxyethylene ether chain number 7) and 1 part by mass of antistatic agent (methyl trihydroxyethyl methylammonium sulfate) and 1 part by mass of antioxidant (2,2'-methylenebis(4-methyl-6-tert-butylphenol)) were added, and water (378 parts by mass) was added dropwise while mechanically stirring to obtain an emulsion of a cross-linked silicone oil agent based on reversible ionic hydrogen bonds (the concentration of the oil agent in the emulsion was 30 wt%).
[0098] Example 8
[0099] 95 parts by mass of amino-modified polydimethylsiloxane (A) (ma≈65, na≈1, pa=0, ra=0, sa=3, Shin-Etsu Silicone International Trading (Shanghai) Co., Ltd. KF-865) (110 mPa·s, amino content 0.20 mmol / g), 5 parts by mass of monocarboxyl-modified polydimethylsiloxane (B2) (m=10, nc≈14, Dow Corning DOWSIL TM BY 16-750 Fluid) (140 mPa·s, carboxyl content 1.2 mmol / g) was mixed evenly, and then 55 parts by mass of C 12 ~C 18Alcohol polyoxyethylene ether (polyoxyethylene ether chain number is 9, AEO-9), 1 part by mass of antistatic agent (methyl trihydroxyethyl methyl ammonium sulfate) and 1 part by mass of antioxidant (2,2'-methylene bis (4-methyl-6-tert-butylphenol)), water (366 parts by mass) is added dropwise while mechanically stirring to obtain an emulsion of a cross-linked silicone oil agent based on reversible ionic hydrogen bonds (the concentration of the oil agent in the emulsion is 30wt%).
[0100] Example 9
[0101] 92 parts by mass of amino-modified polydimethylsiloxane (A) (ma≈140, na≈3, pa=3, ra=1, sa=2, DY-N322D2 from Shandong Dayi Chemical Co., Ltd.) (680 mPa·s, amino content 0.28 mmol / g) and 8 parts by mass of dicarboxyl-modified polydimethylsiloxane (B1) (self-made, nb≈54, carboxyl content 0.9 mmol / g, viscosity 1600 mPa·s) were mixed uniformly, and then 55 parts by mass of isotridecyl alcohol polyoxyethylene ether (polyoxyethylene ether chain number 7) and 1 part by mass of antistatic agent (methyl trihydroxyethyl methylammonium sulfate) and 1 part by mass of antioxidant (tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester) were added, and water (366 parts by mass) was added dropwise while mechanically stirring to obtain an emulsion of a cross-linked silicone oil agent based on reversible ionic hydrogen bonds (the concentration of the oil agent in the emulsion was 30 wt%).
[0102] Comparative Example 1
[0103] 100 parts by mass of amino-modified polydimethylsiloxane (A) (ma≈140, na≈3, pa=3, ra=1, sa=2, DY-N322D2 of Shandong Dayi Chemical Co., Ltd.) (680 mPa·s, amino content 0.28 mmol / g) were added with 55 parts by mass of isotridecanol polyoxyethylene ether (polyoxyethylene ether chain number 7), 1 part by mass of antistatic agent (methyl trihydroxyethyl methylammonium sulfate) and 1 part by mass of antioxidant ((tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester), and water (366 parts by mass) was added dropwise while mechanically stirring to obtain an emulsion of a non-crosslinked silicone oil agent (the concentration of the oil agent in the emulsion was 30 wt%).
[0104] Comparative Example 2
[0105] 100 parts by mass of amino-modified polydimethylsiloxane (A) (ma≈65, na≈1, pa=0, ra=0, sa=3, Shin-Etsu Silicone International Trading (Shanghai) Co., Ltd. KF-865) (110 mPa·s, amino content 0.20 mmol / g) were added to 55 parts by mass of C 12 ~C 18Alcohol polyoxyethylene ether (polyoxyethylene ether chain number is 9, AEO-9) and 1 part by mass of antistatic agent (methyl trihydroxyethyl methylammonium sulfate) and 1 part by mass of antioxidant (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) are added dropwise with water (366 parts by mass) while mechanically stirring to obtain an emulsion of a non-crosslinked silicone oil agent (the concentration of the oil agent in the emulsion is 30wt%).
[0106] Comparative Example 3
[0107] 100 parts by mass of amino-modified polydimethylsiloxane (A) (ma≈72, na≈3, pa=3, ra=1, sa=2, DY-N322 from Shandong Dayi Chemical Co., Ltd.) (180 mPa·s, amino content 0.5 mmol / g) was added to 55 parts by mass of C 12 ~C 18 Alcohol polyoxyethylene ether (polyoxyethylene ether chain number is 9, AEO-9) and 1 part by mass of antistatic agent (methyl trihydroxyethyl methylammonium sulfate) and 1 part by mass of antioxidant (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) are added dropwise with water (366 parts by mass) while mechanically stirring to obtain an emulsion of a non-crosslinked silicone oil agent (the concentration of the oil agent in the emulsion is 30wt%).
[0108] Comparative Example 4
[0109] 100 parts by mass of dicarboxyl-modified polydimethylsiloxane (B1) (self-made, nb≈54, carboxyl content of 0.9 mmol / g, viscosity of 1600 mPa·s) were added to 55 parts by mass of C 12 ~C 18 Alcohol polyoxyethylene ether (polyoxyethylene ether chain number is 9, AEO-9) and 1 part by mass of antistatic agent (methyl trihydroxyethyl methylammonium sulfate) and 1 part by mass of antioxidant (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) are added dropwise with water (366 parts by mass) while mechanically stirring to obtain an emulsion of a non-crosslinked silicone oil agent (the concentration of the oil agent in the emulsion is 30wt%).
[0110] Comparative Example 5
[0111] 100 parts by mass of monocarboxyl-modified polydimethylsiloxane (B2) (m=10, nc≈14, Dow Corning DOWSIL TM BY16-750 Fluid) (140 mPa·s, carboxyl content 1.2 mmol / g), add 55 parts by mass of C 12 ~C 18Alcohol polyoxyethylene ether (polyoxyethylene ether chain number is 9, AEO-9) and 1 part by mass of antistatic agent (methyl trihydroxyethyl methylammonium sulfate) and 1 part by mass of antioxidant (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) are added dropwise with water (366 parts by mass) while mechanically stirring to obtain an emulsion of a non-crosslinked silicone oil agent (the concentration of the oil agent in the emulsion is 30wt%).
[0112] Comparative Example 6
[0113] 50 parts by mass of amino-modified polydimethylsiloxane (A) (ma≈72, na≈3, pa=3, ra=1, sa=2, DY-N322 of Shandong Dayi Chemical Co., Ltd.) (180 mPa·s, amino content 0.5 mmol / g) and 50 parts by mass of dicarboxyl-modified polydimethylsiloxane (B1) (self-made, nb≈54, carboxyl content 0.9 mmol / g, viscosity 1600 mPa·s) were mixed uniformly, and then 60 parts by mass of isotridecyl alcohol polyoxyethylene ether (polyoxyethylene ether chain number 7) and 1 part by mass of antistatic agent (methyl trihydroxyethyl methylammonium sulfate) and 1 part by mass of antioxidant (2,2'-methylenebis(4-methyl-6-tert-butylphenol)) were added, and water (378 parts by mass) was added dropwise while mechanically stirring to obtain an emulsion of a cross-linked silicone oil agent based on reversible ionic hydrogen bonds (the concentration of the oil agent in the emulsion was 30 wt%). (The molar ratio of carboxyl to amino is 1.8)
[0114] Comparative Example 7
[0115] 92 parts by mass of amino-modified polydimethylsiloxane (A) (ma≈72, na≈3, pa=3, ra=1, sa=2, DY-N322 from Shandong Dayi Chemical Co., Ltd.) (180 mPa·s, amino content 0.5 mmol / g) and 8 parts by mass of dicarboxyl-modified polydimethylsiloxane (B1) (self-made, nb≈54, carboxyl content 0.9 mmol / g, viscosity 1600 mPa·s) were mixed uniformly, and then 60 parts by mass of isotridecyl alcohol polyoxyethylene ether (polyoxyethylene ether chain number 7) and 1 part by mass of antistatic agent (methyl trihydroxyethyl methylammonium sulfate) and 1 part by mass of antioxidant (2,2'-methylenebis(4-methyl-6-tert-butylphenol)) were added, and water (378 parts by mass) was added dropwise while mechanically stirring to obtain an emulsion of a cross-linked silicone oil agent based on reversible ionic hydrogen bonds (the concentration of the oil agent in the emulsion was 30 wt%). (The molar ratio of carboxyl to amino is 0.16)
[0116] Comparative Example 8
[0117] 55 parts by weight of amino-modified polydimethylsiloxane (A) (ma≈72, na≈3, pa=3, ra=1, sa=2, DY-N322 from Shandong Dayi Chemical Co., Ltd.) (180 mPa·s, amino content 0.5 mmol / g), 45 parts by weight of epoxy-modified polydimethylsiloxane (structural formula: Figure 1 )nd≈45X-22-163B (60mPa·s, epoxy group content 0.55mmol / g) from Shin-Etsu Silicone International Trading (Shanghai) Co., Ltd., 70 parts by mass of C 12 ~C 18 Alcohol polyoxyethylene ether (polyoxyethylene ether chain number is 9, AEO-9) and 1 part by mass of antistatic agent (methyl trihydroxyethyl methylammonium sulfate) and 1 part by mass of antioxidant (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) are added dropwise with water (401 parts by mass) while mechanically stirring to obtain an emulsion of a cross-linked silicone oil agent (the concentration of the oil agent in the emulsion is 30wt%).
[0118] The preparation process of carbon fiber precursor generally includes polymerization, spinning, coagulation, washing, hot water drawing, oiling, drying, steam drawing, heat setting, and collecting. The organosilicon spinning oil of the present invention is used in the above-mentioned oiling process, and is carried out by immersion and rolling. A secondary oiling process is adopted. The mass concentration of the oil working liquid is 1.2wt%. After the oiling is completed, the precursor is dried at 130°C. The oiling rate of the precursor is 0.5-1.5wt%. If the oiling rate is lower than 0.5wt%, adhesion and broken wires will occur during the pre-oxidation process; if the oiling rate is higher than 1.5wt%, the dispersion of the precursor will deteriorate, resulting in uneven pre-oxidation and reduced carbon fiber performance.
[0119] All the above embodiments and comparative examples were carried out on 6K tows, and the evaluation of the use of the oil emulsion on the carbon fiber production line is shown in Table 1.
[0120] Table 1 Evaluation results of online use of the oil emulsions prepared in the examples and comparative examples
[0121]
[0122]
[0123] As can be seen from Table 1, the oil components of Comparative Examples 1-3 contain only amino-modified polydimethylsiloxane, and the oil components of Comparative Examples 4 and 5 contain only carboxyl-modified polydimethylsiloxane. The cross-linking degree of the oil is low, and the oil film is easy to flow during the pre-oxidation process, which easily causes the oil film to be unevenly distributed on the surface of the pre-oxidized silk fiber, which is reflected in the final carbon fiber strength being less than 5000MPa, which is at a low level. In Comparative Example 6, the molar ratio of the carboxyl content in the carboxyl-modified polydimethylsiloxane to the amino content in the amino-modified polydimethylsiloxane is greater than 1.0, and the bundle of the original silk is poor; while in Comparative Example 7, the molar ratio of the carboxyl content in the carboxyl-modified polydimethylsiloxane to the amino content in the amino-modified polydimethylsiloxane is less than 0.2, the cross-linking degree is too low, and the final carbon fiber strength is less than 5000MPa. From Comparative Example 8 and Example 1, although epoxy-modified polydimethylsiloxane can undergo cross-linking reaction with amino-modified polydimethylsiloxane, the degree of oil cross-linking is high, and the final carbon fiber strength is greater than 5000 MPa, it sticks seriously to the drying roller during the spinning stage.
[0124] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, and without the need to carry out unnecessary experimental conditions, the present invention can be implemented in a wide range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principles of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departure from the disclosed scope in the application, and changes made with conventional techniques known in the art.
Claims
1. A cross-linked silicone oil based on reversible ionic hydrogen bonds, comprising a base component, a nonionic emulsifier and an auxiliary agent, in, The base component comprises: amino-modified polydimethylsiloxane (A) and carboxyl-modified polydimethylsiloxane (B) as shown in formula (1a), The carboxyl-modified polydimethylsiloxane (B) is at least one selected from the group consisting of a dicarboxyl-terminated polydimethylsiloxane (B1) represented by formula (2b) and a monocarboxyl-terminated polydimethylsiloxane (B2) represented by formula (3c); The molar ratio of the carboxyl content in the carboxyl-modified polydimethylsiloxane (B) to the amino content in the amino-modified polydimethylsiloxane (A) is 0.2 or more and 1.0 or less; In formula (1a), ma is any number greater than 1; na is any number greater than 1; ra is 0 or 1; when ra is 0, pa is 0; when ra is 1, pa is any number greater than 1 and less than 5; sa is any number greater than 1 and less than 5; In formula (2b), nb is any number greater than 1; In formula (3c), nc is any number greater than 1; m is any number greater than or equal to 1 and less than or equal to 10 (inclusive of 10).
2. The cross-linked silicone oil according to claim 1, characterized in that: In formula (1a), ma is any number greater than 10 and less than 300; na is any number greater than 2 and less than 10; In formula (1a), the dimethylsiloxane units and the methylaminoalkylsiloxane units are randomly arranged; In formula (2b), nb is any number greater than 10 and less than 300; In the formula (3c), nc is an arbitrary number of 5 or more and 200 or less.
3. The cross-linked silicone oil according to claim 1 or 2, characterized in that: The amino-modified polydimethylsiloxane (A) preferably has a dynamic viscosity of 50 mPa·s or more and 3500 mPa·s or less at 25°C; The amino group content of the amino-modified polydimethylsiloxane (A) is 0.05 mmol / g or more and 1.0 mmol / g or less.
4. The cross-linked silicone oil according to claim 1 or 2, characterized in that: The dicarboxyl-terminated polydimethylsiloxane (B1) has a dynamic viscosity of 100 mPa·s or more and 3000 mPa·s or less at 25° C.; the dicarboxyl-terminated polydimethylsiloxane (B1) has a carboxyl content of 0.1 mmol / g or more and 2.0 mmol / g or less; The monocarboxyl-terminated polydimethylsiloxane (B2) preferably has a dynamic viscosity of 50 mPa·s to 2000 mPa·s at 25° C.; and the monocarboxyl-terminated polydimethylsiloxane (B2) has a carboxyl content of 0.05 mmol / g to 1.5 mmol / g.
5. The cross-linked silicone oil according to any one of claims 1 to 4, characterized in that: In the cross-linked silicone oil based on reversible ionic hydrogen bonds, the nonionic emulsifier is selected from one or more of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, oil polyoxyethylene ether, polyoxyethylene sorbitan ester, and alkyl alcohol amide polyoxyethylene ether; The content of the nonionic emulsifier is 10 parts by mass or more and 100 parts by mass or less relative to 100 parts by mass of the essential component.
6. The cross-linked silicone oil according to any one of claims 1 to 5, characterized in that: In the cross-linked organic silicone oil based on reversible ionic hydrogen bonds, the auxiliary agents include antistatic agents and antioxidants.
7. The cross-linked silicone oil according to claim 6, characterized in that: The content of the antioxidant is 0.5 parts by mass or more and 5 parts by mass or less relative to the total mass of the base component and the nonionic emulsifier; The content of the antistatic agent is 0.5 parts by mass or more and 5 parts by mass or less relative to the total mass of the base component and the nonionic emulsifier.
8. Use of the cross-linked silicone oil agent based on reversible ionic hydrogen bonds according to any one of claims 1 to 7 in the manufacture of carbon fibers.
9. An oil treatment liquid suitable for carbon fiber manufacturing, prepared by dispersing the cross-linked silicone oil based on reversible ionic hydrogen bonds according to any one of claims 1 to 7 in water.
10. The oil treatment liquid according to claim 9, characterized in that: The average particle size of the emulsified particles of the oil treatment liquid is 0.01 μm or more and 0.3 μm or less; In the oil treatment liquid, the concentration of the oil is 10 mass % or more and 40 mass % or less.
Citation Information
Patent Citations
Coating carbon fiber precursor oil agent and preparation method thereof
CN107829306A
Carbon fiber oiling agent capable of rapidly cross-linking to form film
CN114622417A